Keris Sebagai Salah Satu Kebudayaan Materi - Priyanto, Priyanto (UI Scholars Hub, 2013)
“Keris” is one of the material culture as collection museum can be assumed as souvenir, fetish, and collection. The Museum should be giving about the meaning of “keris” and its community. Museum not only show subject as material cultural but also show other aspect as social, religious an aspect dayly acktivity of its community.